Study of the anomaly detection on rail by a tachometer generator of a train - Gaku YOSHIKAWA (Nihon Kikai Gakkai ronbunshu)
Most rolling stocks in Japan have tachometer generators on their axle ends. The only function of the tachometer generator is measuring rotational speed of the axle based on the frequency of the output signal. On the other hand, the amplitude of the output signal reflects not only the speed but also the gap between the tachometer-generator sensor and the axle-end gear. First, this paper shows that the amplitude of the output signal can change during running and the amplitude has a strong correlation with the position of the rolling stock. Generally, the sensor is fixed on the axle box and there is a small allowance between the axle box and the axle journal bearing. Therefore, the relative position between the axle box and the axle can change due to the interaction among the bogie, the axle, and the rail. This fact indicates the possibility that the tachometer generators can be used for some sort of anomaly detections. Based on this, this paper shows some experimental results of the anomaly detection on the rail by means of the tachometer generator.